Determinants of Fraud Prevention PT Perkebunan Nusantara XIV Takalar - Karmila, Yusri; Wahad, Abdul; Wahidah. R, Wardatul (PT FORMOSA CENDEKIA GLOBAL, 2024)
The following are the research objectives in accordance with the goals of this study: Examining the following four topics will help us better understand how fraud is prevented: 1) the impact of internal audit; 2) the impact of audit quality; 3) the impact of good corporate governance; and 4) the combined impact of internal audit, internal control, audit quality, and good corporate governance. The effect of Audit Quality, Internal Audit, Good Corporate Governance has a positive and significant effect on Fraud Prevention at PT Perkebunan Nusantara XIV Takalar. PT Perkebunan Nusantara XIV Takalar has the desired rate with good financial quality, therefore with these criteria it can convince stakeholders in making all decisions, one of which is investing in the company.